2004
DOI: 10.2746/0425164044868350
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B protects horses against induced endotoxaemiain vivo

Abstract: Summary Reasons for performing study: A safe, affordable and effective treatment for endotoxaemia in horses is needed in order to reduce the incidence of this potentially fatal condition. Objective: To evaluate the effect of polymyxin B (PMB) on signs of experimentally‐induced endotoxaemia. Hypothesis: PMB ameliorates the adverse effects of endotoxaemia without causing nephrotoxicity. Methods: Four groups of 6 healthy mature horses each received 20 ng endotoxin/kg bwt i.v. over 30 mins. Additionally, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
76
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 19 publications
7
76
2
2
Order By: Relevance
“…Similar to previous studies 15,16,18,21 in adult horses and foals, LPS administration in this study resulted in marked leukopenia and neutropenia. In similar LPS studies 15,18 investigating polymyxin B in adult horses, significantly higher neutrophil counts in the polymyxin B-treated horses, compared with control horses, were detected 1 hour after LPS infusion only when polymyxin B was administered prior to LPS infusion.…”
Section: 33supporting
confidence: 75%
See 4 more Smart Citations
“…Similar to previous studies 15,16,18,21 in adult horses and foals, LPS administration in this study resulted in marked leukopenia and neutropenia. In similar LPS studies 15,18 investigating polymyxin B in adult horses, significantly higher neutrophil counts in the polymyxin B-treated horses, compared with control horses, were detected 1 hour after LPS infusion only when polymyxin B was administered prior to LPS infusion.…”
Section: 33supporting
confidence: 75%
“…29,40 In adult horses, significantly lower serum TNF-α activity was observed in horses that received polymyxin B (5,000 U/kg [2,272.73 U/lb] prior to LPS administration, 1,000 U/kg [454.5 U/lb] prior to LPS administration, and 5,000 U/kg after LPS administration), compared with control horses, with an earlier and more sustained decrease in TNF-α when polymyxin B was administered prior to LPS infusion. 15 Significantly decreased TNF-α concentration was observed in the polymyxin B-treated foals of the study reported here in a similar pattern as the adult horse group that received polymyxin B after LPS infusion. 15 Interestingly, differences in TNF-α concentration between the polymyxin B and control group were not observed until later time points (8 and 24 hours).…”
Section: 33supporting
confidence: 68%
See 3 more Smart Citations